Minimally Invasive Pulmonary Artery Aneurysm Repair Through a Left Anterior Minithoracotomy—an Alternative Approach. Issue 4 (August 2019) - Rahman, Sana; Cook, Gary; Zheng, Jing; Rehman, Atiq
The purpose in this case was to repair a less invasive approach than a standard sternotomy. Workup of asymptomatic patient with computerized tomography scan of chest revealed pulmonary artery aneurysm and transesophageal echocardiography demonstrated flow stagnation in aneurysm. An alternative minimally invasive approach was performed to repair the pulmonary artery aneurysm with plication through a left anterior minithoracotomy using normothermic cardiopulmonary bypass with percutaneous peripheral cannulation, instead of median sternotomy. Post-repair transesophageal echocardiography demonstrated normal flow in the pulmonary artery. The patient had an uneventful postoperative course and was seen in the outpatient clinic with excellent recovery. Minimally invasive repair of pulmonary artery aneurysm through a left anterior minithoracotomy is a feasible alternative approach. Minimally invasive repair of pulmonary artery aneurysm through a left anterior minithoracotomy is a feasible alternative approach.